PENGARUH CUSTOMER EXPERIENCES TERHADAP REVISIT INTENTION DENGAN MEDIASI LEARNING IN MUSEUM DAN VISITOR SATISFACTION DI MUSEUM WAYANG - Intan Audrey Indira Dewi; Dwinita Laksmidewi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
Revitalization of the museum in various cities in Indonesia by the government, including in Jakarta, aims to increase visits. To support this objective, museum needs to do the proper marketing strategies, one through experiential marketing approach.This study aims to reveal the effect of the customer experience on revisit intention with learning in museum and visitor satisfaction as mediation, from the perspective of museum visitors. This research was conducted at Museum Wayang, Jakarta. The result showed that customer experience in terms of five dimensions namely, sense, feel, think, act, and relate have positive effect on revisit intention through learning in museum and visitor satisfaction as mediating variables.